Bacteriome from Pinus arizonica and P. durangensis: Diversity, Comparison of Assemblages, and Overlapping Degree with the Gut Bacterial Community of a Bark Beetle That Kills Pines - Gonzalez-Escobedo, Roman; Briones-Roblero, Carlos I.; Pineda-Mendoza, Rosa M.; Rivera-Orduña, Flor N.; Zúñiga, Gerardo (Frontiers in Microbiology, 2018)
Symbioses between plants and microorganims have been fundamental in the evolution of both groups. The endophytic bacteria associated with conifers have been poorly studied in terms of diversity, ecology and function. Coniferous trees of the genera Larix, Pseudotsugae, Picea and mainly Pinus, are hosts of many insects, including bark beetles and especially the Dendroctonus species. These insects colonize and kill these trees during their life cycle. Several bacteria detected in the gut and cuticle of these insects have been identified as endophytes in conifers. In this study, we characterized and compared the endophytic bacterial diversity in roots, phloem and bark of non-attacked saplings of Pinus arizonica and P. durangensis using 16S rRNA gene pyrosequencing. In addition, we evaluated the degree of taxonomic relatedness, and the association of metabolic function profiles of communities of endophytic bacteria and previously reported gut bacterial communities of D. rhizophagus; a specialized bark beetle that colonizes and kills saplings of these pine species. Our results showed that both pine species share a similar endophytic community. A total of seven bacterial phyla, 14 classes, 26 orders, 43 families, and 51 genera were identified. Enterobacteriaceae was the most abundant family across all samples, followed by Acetobacteraceae and Acidobacteriaceae, which agree with previous studies performed in other pines and conifers. Endophytic communities and that of the insect gut were significantly different, however, the taxonomic relatedness of certain bacterial genera of pines and insect assemblages suggested that some bacteria from pine tissues might be the same as those in the insect gut. Lastly, the metabolic profile using PICRUSt showed there to be a positive association between communities of both pines and insect gut. This study represents the baseline into the knowledge of the endophytic bacterial communities of two of the major hosts affected by D. rhizophagus.